2022
DOI: 10.3390/coatings12081206
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication and Characterization of P-Type Semiconducting Copper Oxide-Based Thin-Film Photoelectrodes for Solar Water Splitting

Abstract: Solar light-driven hydrogen by photocatalytic water splitting over a semiconductor photoelectrode has been considered a promising green energy carrier. P-type semiconducting copper oxides (Cu2O and CuO) have attracted remarkable attention as an efficient photocathode for photoelectrochemical (PEC) water splitting because of their high solar absorptivity and optical band gaps. In this study, CuO thin films were prepared using the sol-gel spin coating method to investigate the effects of aging time and layer dep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 66 publications
0
5
0
Order By: Relevance
“…It was found that the root mean square (RMS) roughness of the thin films increased from 21.6 nm (Cu 2 O) to 33.9 nm (CuO/Cu 2 O at 350 • C) and 46.5 nm (CuO at 500 • C) (Cu 2 O < CuO/Cu 2 O < CuO). We assume that the controlling of thin film thicknesses using the electrolyte temperature affects RMS roughness [40]. Furthermore, since the light absorption properties of thin films play an essential role in PEC performance, we measured the absorbance of Cu 2 O, CuO/Cu 2 O, and CuO thin films using a UV-Vis spectrometer.…”
Section: Morphology and Optical Properties Of Copper Oxide Thin Filmsmentioning
confidence: 99%
See 2 more Smart Citations
“…It was found that the root mean square (RMS) roughness of the thin films increased from 21.6 nm (Cu 2 O) to 33.9 nm (CuO/Cu 2 O at 350 • C) and 46.5 nm (CuO at 500 • C) (Cu 2 O < CuO/Cu 2 O < CuO). We assume that the controlling of thin film thicknesses using the electrolyte temperature affects RMS roughness [40]. Furthermore, since the light absorption properties of thin films play an essential role in PEC performance, we measured the absorbance of Cu 2 O, CuO/Cu 2 O, and CuO thin films using a UV-Vis spectrometer.…”
Section: Morphology and Optical Properties Of Copper Oxide Thin Filmsmentioning
confidence: 99%
“…It is also known that they are a potential electrode material for photovoltaic applications [24] because of their cost-effectiveness, non-toxicity, excellent carrier mobility [25], and high absorption coefficient. Similarly, these advantages make copper oxides suitable as an efficient photoelectrode for PEC water splitting, as shown in Table S1 [26][27][28][29][30][31][32][33][34][35][36][37] and Table S2 [38][39][40]. One crucial obstacle to copper oxides may be their high electron-hole recombination rate, lowering photoconversion efficiencies.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although green hydrogen production from renewable energy sources is considered a promising approach for net-zero carbon emissions [6,7], ~95% of global hydrogen production is based on fossil fuels [8] (i.e., gray or brown hydrogen), releasing carbon emissions [9]. Hence, developing high-efficiency green hydrogen production technologies from water (i.e., electrochemical [10] and photoelectrochemical (PEC) water electrolysis [11,12]) is imperative. In particular, developing novel high-performance electrode materials for the oxygen evolution reaction (OER) for electrochemical and PEC water electrolysis has attracted much attention because its sluggish reaction kinetics retard large-scale hydrogen production [13].…”
Section: Introductionmentioning
confidence: 99%
“…However, despite these promising advantages, the doping of Zn cation in the electrodeposited Cu2O thin film, which has low bandgap energy and good photocatalytic activity, has not been experimentally proven, particularly regarding its electrocatalyst activity for ethanol electrooxidation applications. The aim of the present study was to synthesize Zn-doped Cu2O thin films by an electrodeposition, which is known as versatile method to fabricate metal [15]- [17] and metal oxide film, on indium tin oxide (ITO) substrate. The structure,…”
Section: Introductionmentioning
confidence: 99%